Strong isotope effect in the VUV photodissociation of HOD: A possible origin of D/H isotope heterogeneity in the solar nebula - Luo, Zijie (Sci Adv, 2021)
The deuterium versus hydrogen (D/H) isotopic ratios are important to understand the source of water on Earth and other terrestrial planets. However, the determinations of D/H ratios suggest a hydrogen isotopic diversity in the planetary objects of the solar system. Photochemistry has been suggested as one source of this isotope heterogeneity. Here, we have revealed the photodissociation features of the water isotopologue (HOD) at λ = 120.8 to 121.7 nm. The results show different quantum state populations of OH and OD fragments from HOD photodissociation, suggesting strong isotope effect. The branching ratios of H + OD and D + OH channels display large isotopic fractionation, with ratios of 0.70 ± 0.10 at 121.08 nm and 0.49 ± 0.10 at 121.6 nm. Because water is abundant in the solar nebula, photodissociation of HOD should be an alternative source of the D/H isotope heterogeneity. This isotope effect must be considered in the photochemical models.